Interpretation of dreams - "Freud, sigmund" (New York, 1998)
The Interpretation of Dreams (German: Die Traumdeutung) is an 1899 book by Sigmund Freud, the founder of psychoanalysis, in which the author introduces his theory of the unconscious with respect to dream interpretation, and discusses what would later become the theory of the Oedipus complex. Freud revised the book at least eight times and, in the third edition, added an extensive section which treated dream symbolism very literally, following the influence of Wilhelm Stekel. Freud said of this work, "Insight such as this falls to one's lot but once in a lifetime.
Keywords: Psychology